2022
DOI: 10.1186/s12912-022-00982-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a self-care scale for older adults undergoing hip fracture surgery: the HFS-SC

Abstract: Background The ability to take care of oneself after hip fracture surgery is important for older adults. Various scales have been developed for evaluation of this ability, but a scale specifically focusing on hip fracture has not been developed. The aim of this study was to develop and validate a scale (Hip Fracture Surgery Self-Care Scale, HFS-SC) to evaluate self-care for older adults undergoing hip fracture surgery. Methods The scale was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This model evidenced a satisfactory t for the 4 factors and the 13 questions, allowing us to highlight adequate psychometric properties, so that the FRS scale is valid for the sample of OA in Chile. These results obtained in the ve t indicators (RMSEA, TLI, CFI an NFI) were consistent with other validation studies [28,30].…”
Section: Discussionsupporting
confidence: 91%

Validity and reliability of the fall risk scale for older adults

Cossio-Bolaños,
Vidal-Espinoza,
Caceres-Bahamondes
et al. 2024
Preprint
“…This model evidenced a satisfactory t for the 4 factors and the 13 questions, allowing us to highlight adequate psychometric properties, so that the FRS scale is valid for the sample of OA in Chile. These results obtained in the ve t indicators (RMSEA, TLI, CFI an NFI) were consistent with other validation studies [28,30].…”
Section: Discussionsupporting
confidence: 91%

Validity and reliability of the fall risk scale for older adults

Cossio-Bolaños,
Vidal-Espinoza,
Caceres-Bahamondes
et al. 2024
Preprint
“…The I-CVI of the Chinese version of the HFS-SC was 0.857 to 1 and the S-CVI was 0.932, which were higher than the reference value of content validity, and the content validity was good ( 37 , 38 ). In this study, EFA showed that the Chinese version of the 5-factor explained 66.666% of the total variance, the factor attribution of all items was consistent with that of the original scale ( 21 , 36 ), and the factor loadings for each item were >0.4. Ultimately, the Chinese version of the HFS-SC model was within an acceptable range for all fitness indicators.…”
Section: Discussionmentioning
confidence: 53%
“…value of content validity, and the content validity was good (37,38). In this study, EFA showed that the Chinese version of the 5-factor explained 66.666% of the total variance, the factor attribution of all items was consistent with that of the original scale (21,36), and the factor loadings for each item were >0.4.…”
Section: Symptom Recognition and Managementmentioning
confidence: 52%
See 2 more Smart Citations